Evolusi Fotografi Jurnalistik dalam Krisis Global:Dokumentasi Konflik dan PerubahanIklim pada Tahun 2024 - Mohammad Fadly, S.E, M.M, Mohammad Fadly, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2024)
Currently, in 2024, the world faces a number of urgent global crises. These include armed conflicts in Ukraine, the Middle East, and some African countries, as well as the dire impacts of climate change, such as rising global temperatures, extreme weather, wildfires, and rising sea levels. In this study, we look at how photojournalism will portray the global crisis in 2024, with a special emphasis on climate change and armed conflict. The way photojournalists work has changed and been influenced by advances in camera technology and digital distribution in recent decades. These advancements have given them the ability to capture and disseminateimages from new perspectives. Journalistic photography is essential to record and disseminate information about the global crisis that is occurring. Photos of conflict zones and areas affected by climate change can convey realities that are often difficult to describe in words. The photographs produced and published succeeded in fostering empathy, raising awareness, and encouraging international action. This study examines how new technologies affect journalistic work and as a result, the role of photojournalism in raising awareness and influencing policies about global crises, ethical issues, safety, and information validity in the digital age. Case studies, in-depth interviews with photojournalists, and content analysis from news sites and social media were the qualitative methods used in this study. Studies show that the use of drones, high-resolution cameras, and other photographic technologies has improved the ability of journalists to document crises around the world. However, ethics, privacy, truth, and safety of journalists are still issues. The study emphasizes that to reach a wider audience and drive faster global action, better safety protocols, support for the well-being of journalists, and more effective distribution strategies are essential